Fertility Assimilation of Immigrants: Evidence from Count Data Models - Jochen Mayer; Regina T. Riphahn (Institute for the Study of Labor (IZA), 1999)
This study applies count data estimation techniques to investigate the fertility adjustment of immigrants in the destination country. Data on completed fertility are taken from the 1996 wave of the German Socioeconomic Panel (GSOEP). While the economic literature stresses the role of prices and incomes as determinants of fertility, the demographic literature discusses whether assimilation or disruption effects dominate immigrants? fertility after migration. We find evidence in favor of the assimilation model according to which immigrant fertility converges to native levels over time. In addition, we confirm the negative impact of female human capital on fertility outcomes.
Keywords: J13; C25; J61; 330; Count data estimation; immigrant fertility; assimilation; disruption; Einwanderung; Fruchtbarkeit; Soziale Integration; Schätzung; Deutschland